Multidose pharmacokinetics of orally administered florfenicol in the channel catfish (Ictalurus punctatus). Issue 5 (8th August 2012) - Gaunt, P. S.; Langston, C.; Wrzesinski, C.; Gao, D.; Adams, P.; Crouch, L.; Sweeney, D.; Endris, R.
Abstract : Plasma disposition of florfenicol in channel catfish was investigated after an oral multidose (10 mg/kg for 10 days) administration in freshwater at water temperatures ranging from 24.7 to 25.9 °C. Florfenicol concentrations in plasma were analyzed by means of liquid chromatography with MS/MS detection. After the administration of florfenicol, the mean terminal half‐life ( t 1/2 ), maximum concentration at steady‐state ( C ss (max)), time of C ss (max) ( T max ), minimal concentration at steady‐state ( C ss (min)), and V c / F were 9.0 h, 9.72 μg/mL, 8 h, 2.53 μg/mL, and 0.653 L/kg, respectively. These results suggest that florfenicol administered orally at 10 mg/kg body weight for 10 days could be expected to control catfish bacterial pathogens inhibited in vitro by a minimal inhibitory concentration value of <2.5 μg/mL.